Hearing Loss in Children: Prevalence, Causes, and Management - Nassar Jabbar Mokhtath Al- Najem (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Hearing loss is a common neonatal abnormality where early detection is crucial for normal speech and language development. Specific Background Children referred to audiology clinics often present with diverse impairments that can be objectively evaluated using auditory brainstem response testing. Knowledge Gap The specific incidence, severity distribution, and anatomical location of auditory deficits within this referred pediatric population require continuous clinical documentation. Aims This study aims to determine the incidence, severity, and location of auditory impairment in youth referred for assessment. Results Among 309 patients aged 1 to 17 years undergoing testing, 91.3% exhibited impairment, whereas 8.7% demonstrated normal bilateral function. Within the impaired cohort, 56% were male and 44% were female. Profound and severe degrees of impairment occurred most frequently, with both ears being predominantly affected. Novelty The documented burden of profound bilateral deficits in this specific clinical cohort highlights critical sex-based and severity distribution trends. Implications These findings strongly support the urgent need for universal newborn screening and early targeted rehabilitation, including cochlear implantation, to prevent irreversible language delays. Highlights A vast majority of referred patients exhibited significant auditory impairment. Profound bilateral deficits frequently presented during clinical assessments. Prompt cochlear implantation prevents permanent language development delays Keywords: Auditory Brainstem Response, Cochlear Implantation, Universal Newborn Screening, Language Development, Pediatric Audiology